Peer and team assessment: Strategies and applications in engineering courses - Nagai, Walter Aoiama (2019)
Teamwork is one of the competencies that more often are referred has required to professional practice in Engineering. Working in teams in the learning process has been referred to be an effective way to promote the development of technical competencies while promoting the development of teamwork competencies. The students identify teamwork as motivating for their self-learning. In a teamwork environment student can deal with self-knowledge, critical analysis, knowledge of the others, individual and group performances, feedback, resilience, synergy, decision making, commitment, participation, self-esteem, leadership, and entrepreneurship. All these characteristics come from the understanding that a team is formed by individuals with different experiences, origins and individual profiles. But what are the criteria for peer or teamwork assessment? Which methods give fair rewards for different contributions to the team and its peers? There are several peer assessments studies where many experiences are described, but there are not many studies that compare the strategies of peer assessments between them. For example, when the criteria have different weights or when the scores given by the peers are anonymous or when the scores are decided by the group, and so on. The objective of this work is to describe several strategies of peer and team assessment, considering the categorization and organization carried out in order to assumptions and/or purposes of each strategy. Thus, a contribution will be made for increasing peer and teamwork assessment in Engineering courses.